Eksistensi Kearifan Lokal Bali Pada Kurikulum Merdeka di Sekolah Dasar - Wahyuni, Luh Tu Selpi; Lestari, Nyoman Ayu Putri; Dharma, I Made Aditya; Lasmawan, I Wayan; Suastra, I Wayan (Jurnal Paedagogy, 2023)
This study aims to analyze the existence of Balinese local wisdom, which is still being inserted into elementary school students learning in the Merdeka Curriculum. The research method used library research by prioritizing integrity, the accuracy of sources, relationships, meaning and suitability with the research focus. The data collection technique for this research was to study documentation articles indexed by Sinta and Scopus related to Balinese local wisdom in the Merdeka Curriculum and analyzed descriptively qualitatively. The results of this study indicated that: (1) Local wisdom in Bali remained timeless and sustainable when applied to learning in elementary schools, despite curriculum changes occurring every five years, (2) Balinese local wisdom, such as Tri Hita Karana and ethnomatics, continued to be incorporated into the curriculum, (3) science and mathematics were identified as subjects in the Merdeka curriculum that could be integrated with Balinese local wisdom, (4) Civics and Indonesian were identified as areas where Balinese local wisdom was not sufficiently applied in the Merdeka curriculum, and (5) traditional games and values in Balinese folklore were found to be aspects of Balinese local wisdom that were not adequately integrated into elementary school learning.